Mannan-BAM, TLR Ligands, Anti-CD40 Antibody (MBTA) Vaccine Immunotherapy: A Review of Current Evidence and Applications in Glioblastoma - Lookian, Pashayar P; Zhao, David; Medina, Rogelio; Wang, Herui; Zenka, Jan; Gilbert, Mark R; Pacak, Karel; Zhuang, Zhengping (International journal of molecular sciences, 2021)
The foundation of precision immunotherapy in oncology is rooted in computational biology and patient-derived sample sequencing to enrich for and target immunogenic epitopes. Discovery of these tumor-specific epitopes through tumor sequencing has revolutionized patient outcomes in many types of cancers that were previously untreatable. However, these therapeutic successes are far from universal, especially with cancers that carry high intratumoral heterogeneity such as glioblastoma (GBM). Herein, we present the technical aspects of Mannan-BAM, TLR Ligands, Anti-CD40 Antibody (MBTA) vaccine immunotherapy, an investigational therapeutic that potentially circumvents the need for in silico tumor-neoantigen enrichment. We then review the most promising GBM vaccination strategies to contextualize the MBTA vaccine. By reviewing current evidence using translational tumor models supporting MBTA vaccination, we evaluate the underlying principles that validate its clinical applicability. Finally, we showcase the translational potential of MBTA vaccination as a potential immunotherapy in GBM, along with established surgical and immunologic cancer treatment paradigms.
Keywords: Ligands; nádory mozku; Toll-like receptor; glioblastoma; Epitopes; Humans; ligandy; T cell; Brain Neoplasms; Toll-like receptor ligands; innate immunity; imunofenotypizace; výsledek terapie; Antigen-Presenting Cells; antigeny CD40; lidé; CD40 Antigens; Immunotherapy; zvířata; metastatic; myši; neutrophil; glioblastom; výpočetní biologie; peptidy; Mice; mannan-BAM; Peptides; Computational Biology; Immunophenotyping; metastázy nádorů; Neoplasm Metastasis; immunotherapy; protinádorové vakcíny; Treatment Outcome; lékařská onkologie; Cancer Vaccines; anti-CD40; Glioblastoma; pathogen-associated molecular patterns; adaptive immunity; Animals; antigen prezentující buňky; epitopy; imunoterapie; Medical Oncology